Design and construction of a low cost air purifier for killing harmful airborne microorganisms using a combination of a strong multi-directional electric-field and an ultra violet light. (April 2022) - Ruwan Jayakantha, D.N.P.; Bandara, H.M.N.; Gunawardana, Nadeesha M.; Jayantha Rajapakse, R.P.V.; Thilakarathne, Dulari S.; Comini, Elisabetta; Gunawardhana, Nanda; Karunarathne, S.M.M.L.
Abstract: In this work we have designed and developed a low cost and simple instrument to purify air in an enclosure. The device sucks up the air in the enclosed area, kills the microorganisms and let clean air flow out. A combination of an ultra violet light and an electric field are used to kill the microorganisms in air. Three electric field chambers (radial, parallel, perpendicular) are used to clean air more effectively. Stainless steel meshes were used to increase the density of the electric fields. The outer covers were made with plastic and wood. The instrument was tested against an evaporated bacterial solution (Staphylococcus aureus) by letting it flow through the instrument and measuring the bacterial concentration of the output air. The results showed the instrument is extremely effective even when tested against high bacterial concentrations. The instrument is extremely useful to clean air in closed rooms such as in hospitals, schools, etc. and prevent the spread of airborne diseases.